Modern construction management - Harris, Frank (Wiley-Blackwell, 2013)
This new edition of the core textbook for construction managers is thoroughly revised to reflect current best practices and the latest developments in the field. It focuses on new processes now considered essential, including lean construction methods, corporate social responsibility, construction management systems, sustainability, and more.